Kautokeino School, Landskapsmodell - (:unkn) unknown (Chalmers tekniska högskola // Institutionen för arkitektur och samhällsbyggnadsteknik, 2026)
In 2020, a price and design competition was announced for a new Sami children’s and youth school in Kautokeino. The competition brief specified that "Sami's identity, culture, and expression must be reflected in the design of the building. The school should strengthen and develop Sami identity, culture, and language. Furthermore, it was asked that the competition proposals signal Sami identity, both in choice of materials, art and decoration, interior and exterior”. The architecture firm, Holar, won the competition with their project "Nature teaches us”. The new school is a 6000 m2 timber and concrete building. The circle is found in the strong circular shape of the outdoor space, which is formed by the building itself. It is the main architectural feature of the project, and emphasizes the simple square shape of the building. This courtyard is the external heart of the school, turned towards the sun, oriented south west. There is a large activity hall towards the north and a swimming hall towards the east. The Sami curriculum is present in the design as there is a larger focus on outdoor activities.
Kautokeino School, Site model
Keywords: Educational Architecture; Architectural competition; Community space; Sami architecture